2021
DOI: 10.1186/s12933-021-01365-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of subclinical myocardial necrosis using high-sensitivity cardiac troponin T in patients with prediabetes

Abstract: Background Risk stratification of patients with prediabetes is an unmet clinical need. Here, we examine the utility of subclinical myocardial necrosis assessed by high-sensitivity cardiac troponin T (hs-cTnT) in predicting health outcomes in stable subjects with prediabetes. Methods hs-cTnT was analyzed by a high-sensitivity assay (Roche 5th generation) in 2631 stable subjects with prediabetes (HbA1c 5.7–6.4% or fasting glucose 100–125 mg/dL withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…In Table 1, we reported an insignificant negative association between HbA1c and the cardiac troponin (cTnT and cTnI) in the NPD group, whereas the association was positive in the PD group. This study is per a recently published study by Witkowski et al, in which prediabetes is associated with adverse cardiac events (MACE) and increasing hs-cTnT levels associated with an increased risk for 3-year MACE and 5-year all-cause mortality in the entire cohort [68].Interestingly, there was no correlation between the levels of hs-cTnT and either FBG or HbA1c [69]. Matsumoto observed a significant positive correlation between HbA1c and hs-cTnT in participants with T2DM.…”
Section: Nox1 Elevation Risks Myocardial Injury and Myocardial Infarc...supporting
confidence: 80%
“…In Table 1, we reported an insignificant negative association between HbA1c and the cardiac troponin (cTnT and cTnI) in the NPD group, whereas the association was positive in the PD group. This study is per a recently published study by Witkowski et al, in which prediabetes is associated with adverse cardiac events (MACE) and increasing hs-cTnT levels associated with an increased risk for 3-year MACE and 5-year all-cause mortality in the entire cohort [68].Interestingly, there was no correlation between the levels of hs-cTnT and either FBG or HbA1c [69]. Matsumoto observed a significant positive correlation between HbA1c and hs-cTnT in participants with T2DM.…”
Section: Nox1 Elevation Risks Myocardial Injury and Myocardial Infarc...supporting
confidence: 80%
“…Chronically elevated troponin levels are an elevated risk of cardiovascular events and a symptom of subclinical myocardial damage, overall mortality, and a number of illnesses, including (pre) diabetes (13,16) .…”
Section: Discussionmentioning
confidence: 99%
“…With a median level of 13 ng/L, Witkowski et al (13) showed that prediabetics had a high prevalence of hs-cTnT. Also, a greater risk of long-term unfavourable cardiovascular events was also demonstrated in stable prediabetic subjects with subclinical myocardial necrosis as determined by hs-cTnT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…an unfavorable prognosis [38][39][40][41]; 4) Diagnostic significance of CTs concentrations in urine and oral fluid (saliva) in case of CVDs [42][43][44][45][46][47]. This new field of noninvasive diagnostics and monitoring of CVDs has promising prospects due to a number of advantages associated with obtaining biomaterial.…”
Section: Introduction: Biochemistry and Diagnostic Contribution Of Ca...mentioning
confidence: 99%